2020
DOI: 10.20944/preprints202008.0718.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinically Relevant Germline Mutations in a Cohort of Young Women with Breast Cancer: A Comprehensive Analysis of Hereditary-Cancer Genes from Whole-Exome Sequencing

Abstract: Young women with breast cancer represent 15% of cancer cases in Latin America. Genomic studies have found that early-onset breast-cancer cases exhibit a higher genetic susceptibility and a specific genomic signature as compared to their older counterparts. The aim of this study was to describe clinically relevant germline mutations in a cohort of young women with breast cancer. To achieve this, we analyzed hereditary-cancer genes from whole-exome sequencing data in 108 unrelated women with an extreme phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A comparative analysis took place between frequent reported variants observed in YWBC from LA countries [ 32 , 78 ] and reported variants from databases such as TCGA, METABRIC, COSMIC, and CCLE. Variant selection for this study is shown in Figure 10 .…”
Section: Methodsmentioning
confidence: 99%
“…A comparative analysis took place between frequent reported variants observed in YWBC from LA countries [ 32 , 78 ] and reported variants from databases such as TCGA, METABRIC, COSMIC, and CCLE. Variant selection for this study is shown in Figure 10 .…”
Section: Methodsmentioning
confidence: 99%